The option trader’s guide to probability, volatility, and timing - Kaeppel, Jay (John Wiley & Sons, 2002)
The Option Traders Guide to Probability, Volatility, and Timing will introduce you to the most important concepts in options trading and provide you with a working knowledge of various options strategies that are appropriate for any given situation. Whether youre a new trader or "returnee" to the options market, this book will not just teach you about options, it will teach you how to successfully trade them